Effect of socio demographic and personal factors on infertility and its association with mental health and social support in North Indian population - Singh, Neetu; Singh, Jyotsna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Motherhood is a bliss in women’s lives and thus infertility is considered as a social stigma. In present study, we measure the effect of socio-demographic and personal factors on infertility as well as the status of social support and mental health in infertile women. Methods: This was a cross-sectional study comprising 90 infertile women and 90 women in the control group, conducted at Ram Prakash Gupta Memorial Mother and Child State Referral Centre of RMLIMS, Lucknow, India. The questionnaires used were Socio-demographic and personal characteristics, General Health Questionnaire (GHQ-12) to assess mental health, Perceived Social Support Questionnaire (PSSQ). To determine the relationship between socio-demographic characteristics, personal characters, mental health, and social support with infertility, Chi-square test was used. Results: Age, education, and occupation had statistically significant (p<0.05) relation with infertility, high BMI, and caffeine intake also had the significant adverse effect on fertility outcomes (p<0.05). Infertility patients had poor mental health status (higher mean GHQ-12 score 20.8±4.2) and poor perceived social support (lower mean PSSQ score 29.7±7.0). Conclusions: In present study, the socio-demographic factors, lifestyle factors, social support and mental health status is associated with fertility outcomes. Their modifications have the potential to improve reproductive performances. A structured programme of education, social support, and counselling by specialist health professionals should be formulated to improve the quality of life as well as fertility outcomes in infertile patients.